Examining the ability of Advanced Systems of Wireless Communication Enhanced by IRS Technology - Razzaque, Md. Abdur; Mahmud, Ashek Raihan; Islam, Md. Shariful (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
Intelligent Reflecting Surfaces (IRSs) represents a pivotal component of technology, facilitating the enhancement of wireless communication performance and the manipulation of electromagnetic propagation environment. IRS technology has the remarkable capability to transform wireless channels from highly probabilistic to notably deterministic, effectively mitigating the substantial losses encountered in the millimeterwave (mmWave) band. Our analysis emphasizes how this innovative technology has ushered in a new era in wireless communications. Within the scope of this study, we delved into investigating the effectiveness of IRSassisted wireless transmissions across various scenarios, encompassing both line-of-sight (LOS) and non-line-of-sight (NLOS) conditions. Our investigation involved the simulation of a 32×32 IRS array with a wavelength of 1 meter and an incident angle of 45 degrees. By manipulating the phase shifts of individual IRS elements, we examined their impact on achievable data rates concerning the number of elements. We also explored the relationship between throughput and separation distances, highlighting the significance of IRS placement in achieving optimal data rates. Channel capacity analysis was conducted for single IRS configurations with 50 and 100 elements, as well as dual IRS setups, shedding light on the capacity improvements achievable in different arrangements. Additionally, our study delved into Bit Error Rate (BER) performance in cooperative doubled IRS-aided wireless communication, employing a range of digital modulation techniques across various Signal-to-Noise Ratio (SNR) levels. This insight offers a valuable perspective on the reliability of IRS-aided systems across diverse modulation schemes. We also undertook a comprehensive Spectral Efficiency (SE) analysis, investigating IRS-assisted Multiple-Input, Single-Output (MISO) and Multiple-Input, Multiple-Output (MIMO) communications using various modulation schemes. Finally, we examined path loss characteristics across indoor encompassing different environments, especially at 20 GHz and 28 GHz using vertical to vertical (V-V) polarization. The culmination of this thorough simulation study underscores the tremendous potential of IRS technology in revolutionizing wireless communication across diverse scenarios, offering invaluable insights for future design and development endeavors.